Mobile application to calculate fidyah with cloud computing / Awais Karni Ahmad - Awais Karni, Ahmad (2016)
Mobile application to calculate fidyah with cloud computing is a project to help students in solving the problem in calculating the fidyah, some Muslim does not know how to calculate fidyah. Fidyah is a fine for Muslim who did not perfonned fasting in the month of Ramadhan for certain reason. Besides that, some of them also do not know what is the price rate for one cupak of rice. They need the information in order to pay their fidyah. This project tried to find solution to help students by creating the best application to calculate the fidyah. In addition the application developed in this project will provide price rate in the calculation. In the application it will used cloud computing technology to synchronize the price rate of one cupak of rice among application client so the application will receive the latest price rate without updating the whole application. In future work, this project hopes that it will improved the application functionality by providing save function for students to save their calculated result for future reference. Besides that the application also can be improved by making notification for students to pay fidyah.